Effect of the reduction process on the field emission performance of reduced graphene oxide cathodes. Issue 66 (19th July 2015) - Sygellou, Labrini; Viskadouros, George; Petridis, Costas; Kymakis, Emmanuel; Galiotis, Costas; Tasis, Dimitrios; Stratakis, Emmanuel
<x xml:space="preserve">Abstract</x> The effect of the reduction process and oxygen-contained functional groups on the field emission performance of reduced graphene oxide cathodes.